1997
DOI: 10.1007/bf03015361
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes regarding pca and associated costs

Abstract: Patient attitudes regarding pca and associated costsPurpose: To determine patients' knowledge and attitudes towards patient-controlled analgesia (PCA) costs through the use of our acute pain service quality assurance (QA) programme. Methods: Quality Assurance questionnaires were distributed to all patients receiving PCA opio~ds for > 12 hr. Patients were asked to note the presence of side effects (nausea/vomiting, pruritus, urinary retention), to indicate their satisfaction with regard to their pain relief, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In concordance with previous reports [5,17,19,30–32], patients in the current study reported a high rate of satisfaction with the PCA modality of postoperative pain control (as reflected by a median score of 7.5 on the 0–10 scale), regardless of whether the PCA was given epidurally or intravenously. Additionally, when PCA is managed by anesthesiologists, especially those with a focused attention of an acute pain service (as in the current study), patient satisfaction is further enhanced [33].…”
Section: Discussionsupporting
confidence: 92%
“…In concordance with previous reports [5,17,19,30–32], patients in the current study reported a high rate of satisfaction with the PCA modality of postoperative pain control (as reflected by a median score of 7.5 on the 0–10 scale), regardless of whether the PCA was given epidurally or intravenously. Additionally, when PCA is managed by anesthesiologists, especially those with a focused attention of an acute pain service (as in the current study), patient satisfaction is further enhanced [33].…”
Section: Discussionsupporting
confidence: 92%
“…Patient-controlled analgesia (PCA) is an effective form of analgesia where the patient is in control of his/her own pain relief 8 . However there have been reported side-effects associated with the use of PCA such as respiratory depression 9 as well as nausea and vomiting 10 .…”
mentioning
confidence: 99%
“…Those who had higher degrees of satisfaction showed a greater cost from their presurgical bid [5,6]. In the previous study to determine WTP for hip and knee joint replacement surgery, a significant correlation was found between WTP and degree of satisfaction [7].…”
Section: Discussionmentioning
confidence: 99%